An examination of educational institutions' knowledge performance: analysis, implications and outlines for future research - Kumar, Naresh; Idris, Khairuddin (2006)
Purpose - This study aims to explore the relationships between learning organisation dimensions, institutional characteristics and knowledge performance among Malaysian private higher learning institutions. Design/methodology/approach - The researchers sought managers' responses to the dimensions of the learning organisation questionnaire (DLOQ) together with perceived measures of private higher learning institutions' knowledge performance to determine relationships. Findings - It was discovered that there were positive, medium to high, and significant relationships between the seven dimensions of the learning organisation and the dependent variable, perceived knowledge performance. The three dimensions that demonstrated strong relationships were team learning, embedded systems and provision of leadership. The institutional characteristics that jointly affect the private higher learning institutions' performance were perceived level of institutional commitment to institutional/professional service and institutional level of commitment to effective teaching and learning. Originality/value - On the whole, the findings of this study provide empirical information, which supports the concept of the learning organisation and their positive influence on the knowledge performance, especially in the private higher education industry. Implications for research and practice as well as recommendations for future studies were highlighted to facilitate those who were involved in learning research. © Emerald Group Publishing Limited